2014
DOI: 10.1371/journal.pone.0098063
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Regulates Human Foetal Femur Derived Skeletal Stem Cell Differentiation by Down-Regulating SMAD2 and SMAD3

Abstract: MicroRNAs (miRs) play a pivotal role in a variety of biological processes including stem cell differentiation and function. Human foetal femur derived skeletal stem cells (SSCs) display enhanced proliferation and multipotential capacity indicating excellent potential as candidates for tissue engineering applications. This study has examined the expression and role of miRs in human foetal femur derived SSC differentiation along chondrogenic and osteogenic lineages. Cells isolated from the epiphyseal region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 43 publications
2
42
0
1
Order By: Relevance
“…For example, miR-146a was found to be expressed by human fetal femur diaphyseal cells at a significantly higher level compared to epiphyseal populations. Detection of miR146a function in fetal femur cells confirmed regulation of protein translation of SMAD2 and SMAD3, resulting in a down-regulation of the chondrogenesis related gene SOX9 and up-regulation of the osteogenesis related gene RUNX2 [20].…”
Section: Introductionmentioning
confidence: 83%
“…For example, miR-146a was found to be expressed by human fetal femur diaphyseal cells at a significantly higher level compared to epiphyseal populations. Detection of miR146a function in fetal femur cells confirmed regulation of protein translation of SMAD2 and SMAD3, resulting in a down-regulation of the chondrogenesis related gene SOX9 and up-regulation of the osteogenesis related gene RUNX2 [20].…”
Section: Introductionmentioning
confidence: 83%
“…23,26,27 Only a few miRNAs have been found to promote osteogenic differentiation. 25,42,43 In this study, we first identified miR-216a as an important enhancer of osteoblast differentiation of hAMSCs and hucMSCs. In the case of bone formation, MSCs generate new osteoblasts and their progenitors, which are essential for bone homeostasis and fracture healing.…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression of miR‐483 in hMSCs reduced the expression of chondrogenic markers and GAGs production and this effect was shown to be achieved via direct targeting of SMAD4 . miR‐199a* and miR ‐ 146a exert anti‐chondrogenic roles by targeting SMAD1 and SMAD2/3, respectively . Pro‐chondrogenic growth factors other than TGF‐β were also shown to be regulated by miRNAs.…”
Section: Intracellular Anti‐chondrogenic Regulatorsmentioning
confidence: 99%